Pengaruh Atraksi Wisata, Amenitas, dan Aksebilitas terhadap Kepuasan Wisatawan di Kawasan Goa Batu Kapal - Adif, Riandy Mardhika; Putra, Arif Mai Eka; Afrida, Yenti (SAFE-Network, 2023)
This study aims to determine the effect of tourist attractions, amenities, and accessibility on tourist satisfaction in Batu Kapal Caves, South Solok Regency. The type of research used in this research is field research or with a quantitative approach. The processed data is primary data. The subjects of this study were tourists in the southern ship of Batu Kapal Solok. The research instruments used in this study were a questionnaire and a Likert scale. Secondary data was obtained from the Solok Selatan district tourism office. Primary data were obtained from tourist respondents who visited the Batu Caves area of ​​the southern ship of Solok. The results showed that: tourist attractions have a positive and significant effect on tourist satisfaction in the Batu Kapal cave area in South Solok. This is evidenced by the tcount value of 6.137>ttable 1.660 and a significant value of 0.000<0.05. Amenities have a positive and significant effect on tourist satisfaction in the ship rock cave area in South Solok. This is evidenced by the tcount value of 11.123>ttable 1.660 and a significant value of 0.000<0.05. Accessibility has no positive and significant effect on tourist satisfaction in the Batu Kapal cave area in South Solok. This is evidenced by the tcount -1.334<ttable 1.660 and a significant value of 0.185>0.05. Tourist attractions, amenities, and accessibility together have a positive and significant effect on tourist satisfaction in the Batu Kapal cave area in South Solok. This is evidenced by the fcount value of 104.384>ftable 2.70 and a significance value of 0.000<0.05.